Cobalt-doped porous carbon nanofibers with three-dimensional network structures as electrocatalysts for enhancing oxygen reduction reaction. (29th May 2023) - Deng, Nanping; Gao, Hongjing; Wang, Gang; Zhang, Lugang; Wang, Hao; Zeng, Qiang; Yan, Jing; Zheng, Tinglu; Cheng, Bowen; Kang, Weimin
Abstract: In this study, we design and prepare the cobalt-doped porous carbon nanofibers (Co@PCNFs) as efficient electrocatalysts based on the electro-blow spinning method and carbonization processes. The porous Co@PCNFs has the three-dimensional porous carbon network structures as the fast electron transport channels and endow the materials with high specific surface area. The central metal Co atoms will be converted into metal nanoparticles with high efficient catalysis in the PCNFs after the carbonization treatment. And the carbonized product still inherits the nanometer size of the ZIF-67 (40–50 nm) precursor, which is more beneficial to expose more active sites. These advantages enable the prepared electrocatalyst to exhibit excellent oxygen reduction reaction (ORR) performance (onset potential of 0.91 V vs. RHE, half-wave potential of 0.857 V vs. RHE), which is very close to commercial Pt/C. More importantly, the obtained Co@PCNFs catalyst exhibited superior electrochemical stability and methanol tolerance over commercial Pt/C under alkaline conditions. The work will open up novel options for various fields such as high performance Zn-air batteries and fuel cells in the future. Graphical abstract: Image 1 Highlights: Carbon nanofibers with 3D network structures are designed and prepared. The porous structure can be used as a fast transport channel for electrons. Layered pore structure absorbs more O2 and fully contacts the active site. Exhibited better stability than Pt/C catalyst. The half-wave potential of Pt/C catalyst is close to that of the catalyst.